Pushover analysis of unreinforced irregular masonry buildings: Lessons from different modeling approaches - Asikoglu, Abide (2020)
The present paper addresses the seismic performance of a half-scale two-story unreinforced masonry (URM) building with structural irregularity in plan and in elevation. The main objectives are (i) to understand the seismic response of URM buildings with torsional effects, and (ii) to evaluate the reliability of using simplified approaches for irregular masonry buildings. For this purpose, nonlinear static analyses are carried out by using three different modeling approaches, based on a continuum model, beam-based and spring-based macro-element models. The performance of each approach was compared based on capacity curves and global damage patterns. Reasonable agreement was found between numerical predictions and experimental observations. Validation of simplified approaches was generally provided with reference to regular structures but, based on the differences in the base shear capacity found here, it appears that structural irregularities are important to be taken into account for acquiring higher accuracy on simplified methods when torsion is present.